Temperature and pressure dependence of the rain‐snow phase transition over land and ocean - Aiguo Dai (Geophysical Research Letters)
The phase of precipitation is important for weather forecasts, land hydrology and remote sensing. To quantify the temperature and pressure dependence of snow frequency (F, in %) when precipitation occurs, we have analyzed 3‐hourly weather reports of surface air temperature (Ts, °C) and pressure (Ps), and snow and rain occurrences from over 15,000 land stations and available ship observations from 1977–2007. It is found that the phase transition occurs over a fairly wide range of temperature from about −2°C to +4°C over (low‐elevation) land and −3°C to +6°C over ocean. The F‐Ts relationship can be represented by a hyperbolic tangent: F(Ts) = a [tanh (b (Ts – c)) – d], with the slope parameter b close to 0.7 over land and 0.4 over ocean. The pressure‐dependence is only secondary and reflected in the parameters. Results show that snow occurs often (F > 50%) for Ts ≤ 1.2°C over land and Ts ≤ 1.9°C over ocean, and are non‐negligible (F > 5%) for Ts ≤ 3.8°C over land and Ts ≤ 5.5°C over ocean. This “warm bias” results from the falling of snowflakes into warmer surface layers, which is especially true over ocean. The warm bias is higher when air pressure is below ∼750 hPa because snow falls faster in thin air.